A review of input and output policies for cereals production in India - Shreedhar, Ganga; Gupta, Neelmani; Pullabhotla, Hemant; Ganesh-Kumar, Anand; Gulati, Ashok (International Food Policy Research Institute, 2012)
This paper reviews the key policies with regard to agriculture inputs such as seed, fertilizer, water, agricultural equipment, research, extension, and agricultural credit. It also provides an overview of the policies and programs related to agricultural output markets that are crucial for improving cereal production in the country.